Quantifying cell divisions along evolutionary lineages in cancer - Blohmer, Martin; Cheek, David M.; Hung, Wei-Ting; Kessler, Maria; Chatzidimitriou, Foivos; Wang, Jiahe; Hung, William; Lee, I.-Hsiu; Gorelick, Alexander N.; Wassenaar, Emma CE; Yang, Ching-Yeuh; Yeh, Yi-Chen; et al. (Nature genetics, 2025)
Cell division drives somatic evolution but is challenging to quantify. We developed a framework to count cell divisions with DNA replication-related mutations in polyguanine homopolymers. Analyzing 505 samples from 37 patients, we studied the milestones of colorectal cancer evolution. Primary tumors diversify at ~250 divisions from the founder cell, while distant metastasis divergence occurs significantly later, at ~500 divisions. Notably, distant but not lymph node metastases originate from primary tumor regions that have undergone surplus divisions, tying subclonal expansion to metastatic capacity. Then, we analyzed a cohort of 73 multifocal lung cancers and showed that the cell division burden of the tumors’ common ancestor distinguishes independent primary tumors from intrapulmonary metastases and correlates with patient survival. In lung cancer too, metastatic capacity is tied to more extensive proliferation. The cell division history of human cancers is easily accessible using our simple framework and contains valuable biological and clinical information.
Gesehen am 22.10.2025